2001
DOI: 10.1054/bjoc.2000.1678
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of cell proliferation and protease secretion by epidermal growth factor and amphiregulin in tumoral versus normal breast epithelial cells

Abstract: Summary Amphiregulin (AR) is a heparin-binding epidermal growth factor (EGF)-related peptide that seems to play an important role in mammary epithelial cell growth regulation. We have investigated the regulation of AR-gene expression and -protein secretion by EGF in normal breast epithelial cells (HMECs), as well as in the tumoral breast epithelial cell lines MCF-7 and MDA-MB231. EGF induced a dosedependent increase of AR mRNA level in both normal and tumoral cells. Thus, 10 Ϫ8 M EGF stimulated AR expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
6
14
0
Order By: Relevance
“…Both AREG and EREG have been implicated in breast cancer (Bieche et al, 2004;Eltarhouny et al, 2008;Gupta et al, 2007;Kenney et al, 1996b;Kondapaka et al, 1997;Ma et al, 1999;Silvy et al, 2001). High levels of AREG expression have been identified in cancerous lesions but not in neighboring noncancerous tissue (LeJeune et al, 1993;Panico et al, 1996;Qi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both AREG and EREG have been implicated in breast cancer (Bieche et al, 2004;Eltarhouny et al, 2008;Gupta et al, 2007;Kenney et al, 1996b;Kondapaka et al, 1997;Ma et al, 1999;Silvy et al, 2001). High levels of AREG expression have been identified in cancerous lesions but not in neighboring noncancerous tissue (LeJeune et al, 1993;Panico et al, 1996;Qi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both ligands are known activators of the EGF receptor (EGFR); AREG exclusively binds to and signals through EGFR (Shoyab et al, 1989), whereas EREG can also bind to and signal through ERBB4 Shelly et al, 1998). AREG is essential for normal ductal morphogenesis in the mammary gland (Ciarloni et al, 2007;Luetteke et al, 1999) and has also been linked to breast cancer progression (Kenney et al, 1996a;Kondapaka et al, 1997;Ma et al, 1999;Silvy et al, 2001). Studies examining AREG expression in human breast cancers have found AREG expression to significantly correlate with regional lymph node metastases, large tumor size and high-grade tumors (LeJeune et al, 1993;Ma et al, 2001;Qi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between the biological effects of EGF and amphiregulin reveals distinct differences (43). Amphiregulin increases invasion capabilities of MCF-7 breast cancer cells, and transcriptional profiling experiments revealed that amphiregulin and EGF promote dramatically distinct patterns of gene expression (43,44). Several genes involved in cell motility and invasion were up-regulated when nontumorigenic breast epithelial cells were cultivated in the presence of amphiregulin (43).…”
Section: Discussionmentioning
confidence: 99%
“…AR expression was also found to be strongly correlated with inflammatory breast cancer, and a putative AR/EGFR autocrine loop is suggested to contribute to breast cancer progression (30). Indeed, AR may play a specific role in cancer progression, since it has been shown that AR activation of EGFR contributes to the synthesis, secretion, and activation of some proteins involved in invasion and metastasis, such as urokinase-type plasminogen activator, matrix metalloproteinase 9, and extracellular matrix metalloproteinase inducer (31)(32)(33).…”
mentioning
confidence: 99%